Compensation of dynamic electromagnetic field distortion using simultaneous localization and mapping method with application in endobronchial ultrasound‐transbronchial needle aspiration (EBUS‐TBNA) guidance. Issue 1 (26th November 2019) - Navaei Lavasani, Saeedeh; Deevband, Mohammadreza; Farnia, Parastoo; Ahmadian, Alireza; Saghatchi, Samaneh
Abstract: Background: Electromagnetic (EM)‐based navigation methods without line‐of‐sight restrictions may improve lymph node sampling precision in transbronchial needle aspiration (TBNA) procedure. However, EM tracking susceptibility to metallic objects severely declines its precision. Method: We proposed to track the location of a tool in a dynamic bronchial phantom and compensate field distortion in a real‐time procedure. Extended Kalman filter simultaneous localization and mapping (EKF‐SLAM) algorithm employ the bronchial motion and observations of a redundant sensor. The proposed approach was applied to the phantom with four different amplitudes of breathing motion in the presence of two types of field‐distorting objects. Results: The proposed approach improved the accuracy of EM tracking on average from 18.94 ±1.17 mm to 4.59 ±0.29 mm and from 14.2 ±0.69 mm to 4.31 ±0.18mm in the presence of steel and aluminum, respectively. Conclusions: With EM tracking position error reduction based on the EKF‐SLAM technique, the approach is appeared promising for a navigated ultrasound TBNA procedure.